Academic Supervision Strategies of School Principals to Enhance Teacher Performance in Islamic Religious Education Instruction - Guntur Rijaluddin; Ahmad Khori; Muhammad Aditya Firdaus Firdaus (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze the academic supervision strategies implemented by school principals in improving the performance of Islamic Religious Education (IRE) teachers at SMP Plus Persatuan Islam Tanjungsari and SMP Pasundan Tanjungsari. Employing a qualitative case study approach, data were collected through participatory observation, in-depth interviews with principals, teachers, and students, as well as document analysis. Data were analyzed using the interactive model of Miles, Huberman, & Saldaña, while data validity was ensured through triangulation of sources, methods, and time. The findings reveal that principals’ academic supervision strategies include: (1) collaborative supervision, which improved teachers’ contextual lesson plan development skills by 42% and enriched classroom methods; (2) transformational leadership, which enhanced teachers’ intrinsic motivation by 85% through spiritual role modeling and support for digital innovation; (3) the influence of institutional culture, where Islamic-based schools emphasized spirituality while public schools emphasized technical aspects; (4) technology-based innovation, which increased supervision efficiency by 38% and reduced feedback time from 14 days to 4 days, though senior teachers still showed resistance; and (5) multigenerational differentiated supervision, which reduced senior teachers’ resistance to technology by 28% and increased young teachers’ creativity by 41%. This study concludes that academic supervision becomes effective when implemented through a Hybrid Academic Supervision Model, which integrates collaboration, transformational leadership, institutional culture, digital technology, and generational differentiation. This model provides a theoretical contribution to academic supervision literature as well as practical recommendations for school principals in enhancing IRE teachers’ professionalism in the digital era.